2016
DOI: 10.1016/s2214-109x(15)00288-0
|View full text |Cite
|
Sign up to set email alerts
|

Burden of sickle cell trait and disease in the Uganda Sickle Surveillance Study (US3): a cross-sectional study

Abstract: Cincinnati Children's Research Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 27 publications
8
133
1
Order By: Relevance
“…The sickle cell trait (SCT) and disease are more prevalent in subSaharan Africa; in Benin the prevalence is estimated to be 25%, in Nigeria it ranges from 24% to 25%, and in Uganda the trait manifests in up to 30% of the population. [1][2][3][4] Given that about a third of Ghanaians carry the sickle cell gene and about 2% (or 15,000) of newborns in Ghana each year have SCD, the disease presents a heavy public health burden. 5,6 A recent study to explore the attitudes of Ghanaian women to genetic testing for the SCT showed that over half of those who had been tested were still unaware of their status and the majority of those surveyed agreed that pregnant women should undergo testing.…”
Section: Introductionmentioning
confidence: 99%
“…The sickle cell trait (SCT) and disease are more prevalent in subSaharan Africa; in Benin the prevalence is estimated to be 25%, in Nigeria it ranges from 24% to 25%, and in Uganda the trait manifests in up to 30% of the population. [1][2][3][4] Given that about a third of Ghanaians carry the sickle cell gene and about 2% (or 15,000) of newborns in Ghana each year have SCD, the disease presents a heavy public health burden. 5,6 A recent study to explore the attitudes of Ghanaian women to genetic testing for the SCT showed that over half of those who had been tested were still unaware of their status and the majority of those surveyed agreed that pregnant women should undergo testing.…”
Section: Introductionmentioning
confidence: 99%
“…The recently published Uganda Sickle Surveillance (US3) study is the first of its kind to leverage infrastructure from an HIV program for SCA; dried bloodspots collected from HIV-exposed infants were also tested for the presence of sickle cell trait or disease. 25 Vaccination programs are another tremendous health effort that has been successfully rolled out in nearly all countries in the world. Although universal vaccination is not without significant challenges, childhood vaccination rates exceed 80% to 90% in many countries, 26 and this early access point to newborns may provide another opportunity where SCA diagnostics may be implemented, particularly for the large number of children born outside of a hospital.…”
Section: Building On Developed Infrastructurementioning
confidence: 99%
“…1,2 For each DBS sample, the Hb pattern on IEF electrophoresis was scored as normal, trait, disease, or variant; the latter designation required the presence of at least 1 IEF band that did not correlate to the Hb A, Hb F, Hb S, or Hb C controls that were run on each gel and consensus by 2 independent reviewers. Samples that contained sickle Hb and variant Hb were designated as disease, given the potential for clinical manifestations.…”
Section: Variant Samplesmentioning
confidence: 99%
“…The recently published results documented an overall national prevalence of 13.3% sickle trait and 0.7% SCD, but with considerable regional variability. 1 Subsequently, a targeted neonatal screening program has begun in the highest burden districts in the central and northern regions, along with increased emphasis on clinical care and training as part of an emerging national sickle cell strategy for Uganda.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation